Creative AI and Musicking Robots - Vear, Craig (Frontiers in Robotics and AI, 2021)
This article discusses the creative and technical approaches in a performative robot project called Embodied Musicking Robots (2018 – present). The core approach of this project is Human-centred AI (HC-AI) which focuses on the design, development and deployment of intelligent systems that co-operate with humans in real-time in a ‘deep and meaningful way’. [1]. This project applies this goal as a central philosophy from which the concepts of a Creative AI and Experiential Learning are developed. At the centre of this discussion is the articulation of a shift in thinking of what constitutes Creative AI and new HC-AI forms of computational learning from inside the flow of the shared experience between robot and human. The central case study (EMRv1) investigates the technical solutions and artistic potential of AI driven robots co-creating with an improvising human musician (the author) in real-time. This project is ongoing, and currently at v4, with limited conclusions, other than this approach can be felt to be co-operative, but requires further investigation.